Coding telephone numbers to avoid "wrong numbers" - Abaya, Efren F.
"Wrong numbers" are an annoyance for owners of telephones. These incidents are due to several causes, of which the following two may be the most common : (a) pressing the wrong button on a telephone keypad, or (b) misreading a printed or handwritten telephone number. This paper presents two methods for developing numbering plans that will reduce the incidence of accidental wrong numbers when using push-button telephone sets by utilizing an error-detecting code on telephone numbers. It is demonstrated that small telephone numbering plans for 2 digits to 4 digits can be quickly generated by using a weighted code or by exhaustive search. Rotary dial phones are not considered in the paper.